Selective functionalization of hollow nanospheres with acid and base groups for cascade reactions - Gao, J.; Zhang, X.; Lu, Y.; Liu, Shaomin; Liu, Jian (Wiley-VCH Verlag, 2015)
The inner-surface functionalization of hollow silica spheres has rarely been reported and is still a challenging topic. Herein, we report a deacetalization–Henry cascade reaction catalyzed by dual-functionalized mesoporous silica hollow nanospheres with basic amine groups ([BOND]NH2) on the internal shell and carboxylic acid groups ([BOND]COOH) on the external shell. The selective functionalization has been realized by a combination of “step-by-step post-grafting” and “cationic surfactant-assisted selective etching” strategy. Compared to unisolated catalyst, the selectively isolated acidic and basic dual catalyst provides excellent catalytic performance for the deacetalization–Henry cascade reaction in terms of both activity (>99 %) and selectivity (95 %).